Urban Informal Settlements and Access to Public Services: A Case Study of Surabaya - Syarifuddin Abdullah, Ahmad (Generasi Sains Indonesia, 2025)
Urban informal settlements remain one of the most pressing challenges for rapidly growing cities in the Global South, where the expansion of population is not always matched by equitable access to essential services. This study examines the conditions of informal settlements in Surabaya, Indonesia, focusing on how residents access basic public services such as water, sanitation, health care, education, and transportation. A mixed-methods approach was employed, combining household surveys, in-depth interviews, and spatial mapping to capture both quantitative and qualitative dimensions of service provision. The findings reveal persistent inequalities: while electricity and basic education are relatively more accessible due to government programs, services such as clean water, sanitation, and affordable health care remain limited and unevenly distributed. Spatial analysis further shows that most public facilities are concentrated in formal neighborhoods, forcing informal settlement residents to rely on costly or unsafe alternatives. Households also bear a disproportionately high financial burden, as a large share of their income is spent on transportation and education, reinforcing cycles of poverty. Despite these constraints, communities demonstrate resilience through collective strategies, including neighborhood cooperation and partnerships with NGOs, although these measures remain insufficient to address structural exclusion. The study underscores the importance of inclusive urban governance that recognizes informal settlements as integral to the city, calling for targeted investments and policies that promote equity in service delivery.